2013
DOI: 10.1371/journal.pone.0052805
|View full text |Cite
|
Sign up to set email alerts
|

Daytime Sleep Enhances Consolidation of the Spatial but Not Motoric Representation of Motor Sequence Memory

Abstract: Motor sequence learning is known to rely on more than a single process. As the skill develops with practice, two different representations of the sequence are formed: a goal representation built under spatial allocentric coordinates and a movement representation mediated through egocentric motor coordinates. This study aimed to explore the influence of daytime sleep (nap) on consolidation of these two representations. Through the manipulation of an explicit finger sequence learning task and a transfer protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
137
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 125 publications
(160 citation statements)
references
References 61 publications
21
137
2
Order By: Relevance
“…Automatic spindle detection was carried out using a previously published (Fogel, Ray, Binnie, & Owen, 2015;Fogel et al, 2014;Albouy et al, 2013) and validated in-house method employing EEGlab-compatible (Delorme & Makeig, 2004) software (github.com/stuartfogel/ detect_spindles) written for MATLAB R2014a (The MathWorks Inc., Natick, MA). The detailed processing steps and procedures are reported elsewhere and are thus presented only briefly here.…”
Section: Psg Recording and Analysismentioning
confidence: 99%
“…Automatic spindle detection was carried out using a previously published (Fogel, Ray, Binnie, & Owen, 2015;Fogel et al, 2014;Albouy et al, 2013) and validated in-house method employing EEGlab-compatible (Delorme & Makeig, 2004) software (github.com/stuartfogel/ detect_spindles) written for MATLAB R2014a (The MathWorks Inc., Natick, MA). The detailed processing steps and procedures are reported elsewhere and are thus presented only briefly here.…”
Section: Psg Recording and Analysismentioning
confidence: 99%
“…(1) a "goal representation" of the sequence built under spatial, allocentric coordinates and (2) a "movement representation" mediated through egocentric, motor coordinates (Albouy et al, 2013a;Cohen et al, 2005). Interestingly, it has consistently been shown that consolidation of the allocentric (spatial) and egocentric (motor) representations of the sequence depends differently on sleep, suggesting that distinct systems enhance these two different aspects of the memory trace: while consolidation of the spatial representation of the sequence is enhanced following a period of nocturnal (Cohen et al, 2005;Witt et al, 2010) or diurnal (Albouy et al, 2013a) sleep, consolidation of the motor representation does not seem to depend on sleep (Albouy et al, 2013a;Cohen et al, 2005;Hallgato et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has consistently been shown that consolidation of the allocentric (spatial) and egocentric (motor) representations of the sequence depends differently on sleep, suggesting that distinct systems enhance these two different aspects of the memory trace: while consolidation of the spatial representation of the sequence is enhanced following a period of nocturnal (Cohen et al, 2005;Witt et al, 2010) or diurnal (Albouy et al, 2013a) sleep, consolidation of the motor representation does not seem to depend on sleep (Albouy et al, 2013a;Cohen et al, 2005;Hallgato et al, 2013). At the cerebral level, it has been shown that activity in the hippocampus is particularly linked to sleep-dependent consolidation, whereas striatal activity seems to develop in a time-dependent manner (Albouy et al, 2008(Albouy et al, , 2013c; but see Debas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations